Development of docetaxel-loaded (Soluplus®-PF108) mixed micelles vacuum foam-dried product for improved stability and melanoma treatment by QbD approach - Rutuja Chougale; Kiran Patil; John Disouza; Ashok Hajare; Namdeo Jadhav; Popat Kumbhar (SpringerOpen, 2024)
Abstract Background Docetaxel (DTX) finds extensive use in treating various cancers, but its limited solubility, side effects, and multi-drug resistance (MDR) hinder its effectiveness. To enhance DTX's properties, the study aimed to formulate DTX-loaded mixed micelles (MMs) and evaluate their anticancer potential using Quality by Design (QbD) approach. Using solvent evaporation, DTX-loaded MMs were prepared and optimized via a 32 full factorial design. Results The optimized formulation (R5) displayed a % entrapment efficiency (%EE) of 74.81 ± 4.27%, % drug loading capacity (%DLC) of 29.27 ± 0.70%, and mean particle size (MPS) of 71.4 ± 1.24 nm. TEM images confirmed well-dispersed spherical MMs. Analytical studies (IR, DSC, and P-XRD) showed no adverse drug-excipient interactions. The MMs were converted into vacuum foam-dried (VFD) products for enhanced stability. The optimized VFD products exhibited low residual moisture, rapid reconstitution, consistent drug content, and high %EE. Notably, sustained drug release from the VFD product reduced hemolysis and in vitro cytotoxicity against B16F10 melanoma cells. Conclusion This study creatively tackled DTX's challenges through targeted MM development, transformed them into VFD products, demonstrating the potential for melanoma treatment. The QbD approach ensures the formulation's safety, efficacy, and quality, underscoring the promising VFD technology and multifunctionality of mixed micelles. Graphical abstract